Amphibious rice policy and development for climate adaptation effort in Indonesia: integrating bibliometric and field insights - Sulaiman, Andi Amran; Musa, Yunus; Arsyad, Muhammad; Yassi, Amir; Farid, Muh; Bahrun, Abd Haris; Djufry, Fadjry; Dirpan, Andi; Dewi, Iswari Saraswati; Nugraha, Yudhistira; Purwoko, Bambang Sapta; Sembiring, Hasil; et al. (Frontiers Media, 2025)
Amphibious rice varieties are a promising solution to improve rice production resilience under climate change, especially with increasing uncertainty in rainfall patterns. This study uses two complementary methods: bibliometric analysis to explore global research trends on amphibious rice, and field research to optimize the Biobestari variety. The bibliometric analysis identifies key topics, collaborations, and publication patterns. The primary study tests Biobestari using two planting spacing methods, double row with alternating row width (Jajar Legowo is an Indonesian term), square planting and five levels of fertilizer application. The agronomic and economic performance of each combination was evaluated. Results show that amphibious rice, combined with efficient planting and eco-friendly fertilizers, improves productivity and achieves a profit ratio of 1.91. This suggests that amphibious rice is well suited for areas with irregular rainfall. Its adoption should be supported by government programs and farmer training. The study highlights the importance of integrating genetic improvement, good farming practices, economic feasibility, and policy support to build climate-resilient rice systems.